Performance Analysis of an Unsignalized Intersection on the Taman Asri–Tambak Rejo Main Road, Sidoarjo Regency Using the PKJI 2014 Method - Tanarubun, Nanda; Hartatik, Nurani; Firmansyah , Mochammad (CV. Publikasi Indonesia, 2025)
Road intersections are points of conflict that often occur during busy hours. One example of an intersection that is the focus of research is a non-signalized three-way intersection on Taman Asri main road in Sidoarjo Regency with a three-arm intersection type, one direction with 2 lanes, two directions with 4 lanes and a median (324M) located on Taman Asri Main Road, Wadung Asri Road, and Rungkut Mananggal Road. This study aims to analyze vehicle traffic volume, traffic flow capacity, and the performance of the unsignalized three-way intersection on Taman Asri Highway in Sidoarjo Regency using the PKJI (Indonesian Road Capacity Guidelines) method to calculate capacity, degree of saturation, and average delay. The data used include road geometric conditions, traffic volume, capacity, and degree of saturation. Data were collected through field surveys. From the analysis of the research results, the highest traffic volume at the unsignalized intersection on the Taman Asri-Tambak Rejo road segment occurred on Friday afternoon at 4042 vehicles/hour, while the lowest traffic volume occurred on Tuesday noon at 2085 vehicles/hour. The highest capacity was on Monday afternoon at 4391 vehicles/hour with a traffic volume of 3784 vehicles/hour. Meanwhile, the lowest capacity was on Saturday noon at 3649 vehicles/hour with a traffic volume of 2495 vehicles/hour. As for the performance of the unsignalized intersection on the Taman Asri-Tambak Rejo road segment with a type 324 intersection, the peak congestion occurred on Friday afternoon, with a degree of saturation of 0.95, queue probability of 36-72, and a delay of 17.10 seconds; however, this unsignalized intersection is still considered to be in good condition, However the saturation level exceeds the maximum limit, as can be seen from the saturation level reaching 0.95, which exceeds the daily saturation value of 0.85 according to the Indonesian Road Capacity Guidelines (PKJI).